DINAMIK KONSUMSI MAHASISWA PENERIMA KIP KULIAH: PENGARUH GAYA HIDUP, MENTAL ACCOUNITNG, DAN SELF MONITORING - Florence Lisa Hattu; Alfrin Ernest Marthen Usmany (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis, 2025)
Using a quantitative approach with purposive sampling method, data were collected from 84 respondents of 2022-2024 cohorts through online questionnaires and analyzed using multiple linear regression. Results show that lifestyle has a significant positive effect on consumptive behavior (t=4.244; sig.0.000), mental accounting has no effect (t=-1.029; sig.0.307), and self-monitoring has a significant positive effect (t=4.463; sig.0.000). The Adjusted R Square value of 0.448 indicates that the three variables explain 44.8% of the variation in consumptive behavior. These findings indicate that social pressure and the desire for environmental acceptance are more dominant in influencing consumptive behavior than financial categorization ability, thus requiring financial literacy assistance programs and strengthening self-control for KIP Kuliah scholarship recipients. This research extends previous studies by incorporating self-monitoring as a variable and demonstrates its paradoxical positive influence on consumptive behavior in the context of scholarship recipients facing social pressures. Keywords: Consumptive Behavior; KIP Kuliah; Lifestyle; Mental accounting; Self monitoring